PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS MAHASISWA PADA INSTITUTE OF BUSINESS (IOB) DI TIMOR-LESTE - ALARICO BARRETO XIMENES, NATALINO (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.08.TAHUN 2017DO - 10.24843/EEB.2017.v06.i08.p01, 2017)
The aim of this study is to understand the influence of the service quality for the student satisfaction and loyalty. To keep compete on the path, IOB should maintain the good service quality to its students, in order to gain the loyalty from its students. Therefore, with the good quality services, IOB could stand on the competition.           Respondent of this study are the active IOB students, with age minimum 17 years old and maximum 35 years old. The total respondent for this study is 104 respondents, using the purposive sampling technique, and Structural Equation Modeling (SEM) as the data analysis tool. The result of this study showed that the hypothesis put forward entirely acceptable: 1) service quality has positive and significant impact on student satisfaction, 2) service quality has positive and significant impact on student loyalty, 3) student satisfaction has positive and significant impact on student loyalty. Managerial implication from this study is the management of IOB should have regular evaluation for its service quality, and also perform correction and improvement to reduce students complains, in order to increase the student satisfaction and loyalty.